Tutoring as an Experience that Strengthens the Sense of Coherence of Academics - Staszkiewicz, Marzena; Beck-Krala, Ewa (Tutoring akademicki jako doświadczenie wzmacniające poczucie koherencji nauczycieli akademickich, 2025)
Aim: The instability of the modern world and the challenges associated with the increasing demands on academics have become for them a burden with high stress potential. Thus, this paper seeks to understand whether a tutoring process can strengthen academics’ sense of coherence. Methodology: The authors used a desk-based content analysis of the tutoring process documentation and an open-ended survey of a group of tutors at a selected public university in Poland. Results: The results of the study indicate that the academic tutoring process carried out in one of the public universities can strengthen the sense of coherence of academics, and can be influenced by three aspects: comprehensibility, resourcefulness and meaningfulness. Implications and recommendations: Among the key factors influencing the construction of the sense of coherence of academic teachers in the selected university were the support of the university, the support of the community of tutors and also the support of the coordinator of the process. Originality/value: Despite numerous publications on the stressful working environment of academic teachers, no reference could be found to the process of academic tutoring as a tool for enhancing academic teachers’ sense of coherence.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 2, s. 12-23